2008
DOI: 10.2131/jts.33.25
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of carbendazim at low dose levels in male rats

Abstract: -Carbendazim is a systemic broad-spectrum fungicide controlling a wide range of pathogens. It is also used as a preservative in paint, papermaking and leather industry, and as a preservative of fruits. In the present study, low dose intracellular effect of carbendazim was investigated employing 5, 10, 25 and 50 mM of the compound administered to male rats intradermally. Blood and liver of each animal was collected 6 hrs later to analyze serum and tissue enzyme activities, tissue lipid peroxidation and hematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
(20 reference statements)
5
26
1
1
Order By: Relevance
“…This investigation is in tune with the findings of Muthuviveganandavel et al (2008;2011a,b), Zari andAl-Attar (2011), andDikic et al (2012). Min and Kang (2008) reported increased ALT and AST activities in fish hepatocytes treated with benomyl, a carbendazim metabolite.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This investigation is in tune with the findings of Muthuviveganandavel et al (2008;2011a,b), Zari andAl-Attar (2011), andDikic et al (2012). Min and Kang (2008) reported increased ALT and AST activities in fish hepatocytes treated with benomyl, a carbendazim metabolite.…”
Section: Discussionsupporting
confidence: 92%
“…An increase in cholesterol level is a sign of liver damage (Igdedioh and Akinylene 1996). More pronounced than in the present study, carbendazim caused a significant increase in level of cholesterol in rats (Muthuviveganandavel et al 2008;Zari and Al-Attar 2011). Similar to our findings, Selmanoglu et al (2001) observed increased levels of creatinine, cholesterol, and albumin in male rats treated with carbendazim.…”
Section: Discussioncontrasting
confidence: 57%
“…Similarly, [40] reported that thiophanate-methyl fungicide caused an increase in blood urea nitrogen (at 75, 200, and 1200 ppm) and creatinine levels (at 1200 ppm) in rats. This significant rise in creatinine levels was observed in the serum of the male Swiss albino mice after their 4th week of exposure to thimet [21]. The increase in creatinine might be due to impaired kidney function caused by the fungicide.…”
Section: Resultsmentioning
confidence: 82%
“…In addition, oxidative damage in RBC may results from the presence of polyunsaturated fatty acid, heme iron and oxygen 36 . Moreover, Muthuviveganandavel et al (2008) found that red blood cells count significantly decreased in rats treated with 5 and 25 mM Carbendazim, a carbamate pesticide 37 . Such results are consistent with ours.…”
Section: Hematological and Immunological Toxicity Of Carbosulfanmentioning
confidence: 99%